Ethical And Religious Dimensions in the Handling of Sacrificial Animals in Islam - Juniawan Mandala Putra; Muhammad Yusuf; Dicky Wahyudi; Meinorizah Meinorizah (ISTIFHAM, 2026)
This study examines how sacrificial animals (qurban) are managed from the viewpoints of humanitarian principles and Islamic teachings through a systematic review of existing literature. It draws on scholarly articles and field reports published from 2021 to 2025. In Islamic tradition, qurban is a key ritual that involves both spiritual devotion and social and ethical responsibility toward all living creatures. The concept of Ihsan—embodying excellence, compassion, and moral responsibility, as taught by the Prophet Muhammad (peace be upon him)—is central to this framework. In the context of qurban, Ihsan requires Muslims to handle animals humanely, carefully, and with minimal pain, aligning with modern animal welfare standards. Nonetheless, the literature review reveals a gap between ideal teachings and actual practice. Common issues include inadequate hygiene, rough or inappropriate handling, and limited awareness of the spiritual and ethical importance of qurban. These results underscore the necessity for stronger ethical internalization, better technical skills, and comprehensive educational strategies to improve both the humanitarian and spiritual aspects of qurban practices.